Japan : Selected Issues. (IMF Staff Country Reports; Country Report, 2008)
This Selected Issues paper discusses the impact of global financial turmoil on Japan. It describes how close integration in global financial markets has deepened and expanded the channels for spillovers. The paper discusses options for increasing the consumption tax to finance the public pension system. It explains that while parametric reforms have reduced fiscal pressures, the basic pension is becoming a less adequate safety net for the retired. The paper also attempts to explain the declining share of labor income.